2014
DOI: 10.1186/1471-2334-14-137
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic treatment of acute uncomplicated cystitis based on rapid urine test and local epidemiology: lessons from a primary care series

Abstract: BackgroundAcute uncomplicated cystitis (AUC) is an ideal target of optimization for antibiotic therapy in primary care. Because surveillance networks on urinary tract infections (UTI) mix complicated and uncomplicated UTI, reliable epidemiological data on AUC lack. Whether the antibiotic choice should be guided by a rapid urine test (RUT) for leukocytes and nitrites has not been extensively studied in daily practice. The aim of this primary care study was to investigate local epidemiology and RUT-daily use to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 30 publications
1
28
1
1
Order By: Relevance
“…25,26 For fluoroquinolone, we also observed a susceptibility rate of 98%, while the latest published studies in France reported rates of 89%e97%. 25,26 In the study with the lowest susceptibility rate estimates, data had been transmitted by a laboratory network based on urine collected mostly for complicated UTIs, thus resulting in higher resistance rates than observed in the general population. ESBLE represented 1.6% of our sample, which is within the range of the most recently published studies, i.e., 0e3% of UTIs.…”
Section: Discussionmentioning
confidence: 56%
“…25,26 For fluoroquinolone, we also observed a susceptibility rate of 98%, while the latest published studies in France reported rates of 89%e97%. 25,26 In the study with the lowest susceptibility rate estimates, data had been transmitted by a laboratory network based on urine collected mostly for complicated UTIs, thus resulting in higher resistance rates than observed in the general population. ESBLE represented 1.6% of our sample, which is within the range of the most recently published studies, i.e., 0e3% of UTIs.…”
Section: Discussionmentioning
confidence: 56%
“…luoroquinolones (FQs) are broad-spectrum antibiotics commonly used for urinary tract infection (UTI) (1)(2)(3). However, in recent years, a worrisome increase in resistance to FQs has been addressed worldwide (4,5).…”
mentioning
confidence: 99%
“…iprofloxacin (CIP) is one of the agents commonly utilized for treatment of urinary tract infections (UTIs) (1)(2)(3). It is used as an appropriate therapy in patients with UTI not requiring hospitalization in areas where the prevalence of resistance is under 10%.…”
mentioning
confidence: 99%